Reestructuración urbana y arquitectónica de la central de abastos de Villavicencio - Vivas Rojas, Hekaterina; Cardenas Valencia, Estefania (Universidad Antonio Nariño, 2021)
In the municipality of Villavicencio there are 5 market places, the Villavicencio supply center being the most important collection space in the region, these places are located at strategic points in the city and are not in optimal conditions for a good service, for this reason a lousy organization is presented for the sale of these agricultural products. The project called Urban and Architectural Restructuring of the Supply Station (LLANABASTOS) of Villavicencio, is an alternative for the improvement of this plant, providing spaces designed for its clients and its users, as well as striking artisan areas for the cultural impulse of our city , promoting a favorable organization for the reception and distribution of all kinds of agricultural products.